Reliability and validity of motion sensor and radar for measuring shuttlecock velocity in badminton - Phomsoupha, M.; Bonneau, F.; Laffaye, G. (International Journal of Racket Sports Science, 2022)
Radar doppler and inertial measurement unit are often used to analyze the projectile velocity. The aim of the present study was to analyse the reliability and validity of a specifically motion sensor (named: Zepp Tennis) and a radar (Doppler-radar gun) for measuring projectile velocity. Thirty-four (novice, intermediate and expert) stroke badminton smash in a located target. Projectile velocity from five smashes were extracted using Zepp Tennis and Doppler-radar gun data. Between reproducibility of measures was determined by comparing the two sessions. Zepp Tennis and Doppler-radar gun measures were compared with high-frequency video data to establish validity. Both instruments were highly reproducible between trials at different velocity (intra-class correlation coefficient: 0.88-0.94 for radar and 0.78-0.89 for motion sensor). In addition, the positioning of the radar (front of the projectile and angulation) and the placement of the motion sensor and the complexity of the movement (forearm extension and pronation) affect the reproducibility. In terms of validity, radar and motion sensor provides an accurate measure but underestimate projectile velocity (-9.7% and -13.6% respectively).